Synchronous virtual care in children’s health care: a scoping review - Zulla, R. T.; Nicholas, D. B.; Sutherland, S.; Cohen, E.; Birnie, K.; Anthony, S.; Robeson, P.; Selkirk, E.; Killackey, T.; Mohabir, V.; Stinson, J. (Frontiers in Pediatrics, 2025)
ObjectiveSynchronous virtual care comprises real-time, online-mediated healthcare. This approach has increasingly been used in pediatrics, largely implemented in the COVID-19 pandemic. Evidence is limited on the impacts of this mode of care delivery on patient and family experience and care quality. To our knowledge, this is the first scoping review to amalgamate existing knowledge about the perceived impact of synchronous virtual care as it is experienced by children and their families across multiple disciplines.MethodsFollowing guidance from the Joanna Briggs Institute, a search of the peer reviewed, published literature was conducted employing multiple databases: APA PsycInfo, CINAHL, EBSCO, Embase, and OVID. Reviewed articles were published in English from January 1, 2013 to December 31, 2023, and addressed virtual care for children and their families. The initial search generated 1,079 articles, which underwent abstract and then full-text screening. A total of 157 full text articles were screened, yielding 117 articles from which data was extracted.ResultsVirtual care interventions, generally appearing in the last decade (2013–2023), have been largely studied using quantitative approaches. They tend to be positively viewed by youth and parents as indicated by identified benefits and general satisfaction. However, articles report both facilitating and hindering elements of virtual care, and barriers are reported that reflect inequities associated with social determinants of health. Such barriers are shown to impede the use of virtual care among some marginalized communities. The review indicates that effective virtual care approaches require (a) program/organizational infrastructure support, (b) training for both service providers and users, and (c) tailoring to clinical needs.ConclusionConsidering virtual care “fit” for target patients and families is important. Implications for clinical care as well as guidelines for future research are offered.